The effectiveness of the student response system (SRS) in English grammar learning in a flipped English as a foreign language (EFL) class. Issue 8 (17th November 2019) - Liu, Chenchen; Sands-Meyer, Sarah; Audran, Jacques
ABSTRACT: Flipped classes are well-known for reversing the typical in-class lecture and out-of-class homework structure by instructing students to learn by themselves from on-line learning materials and inviting them to ask questions based on their individual difficulties in class. Many attempts at integrating this teaching method into English as a foreign language (EFL) classrooms have proven to be beneficial to students' learning achievement and motivation. However, there is little research on how to organize interactive, engaging and effective in-class activities for an EFL flipped classroom. In this study, a student response system (SRS) is proposed to support teachers in organizing in-class activities in a flipped class. To investigate the effectiveness of this approach, a quasi-experiment was conducted in an EFL classroom in an engineering school. The experimental group used the SRS to do in-class activities while the control group followed the conventional method. The results showed that the use of the SRS increased students' learning motivation and self-efficacy in learning English grammar and improved their participation and engagement in the in-class activities of the flipped learning process. Furthermore, the questionnaire results showed that students accepted the SRS as an instructional method in an EFL flipped class. However, the use of the SRS was not effective in improving students' grammar learning achievement.